Peach PpSnRK1 Participates in Sucrose-Mediated Root Growth Through Auxin Signaling - Zhang, Shuhui; Peng, Futian; Xiao, Yuansong; Wang, Wenru; Wu, Xuelian (Frontiers in Plant Science, 2020)
Sugar signals play a key role in root growth and development. SnRK1 as one of the energy centers, can respond to energy changes in plants, and affect the growth and development of plants. However, studies on sugar signals and SnRK1 regulating root growth in fruit trees have not been reported. In this study, we found that 5% exogenous sucrose could increase the total volume and total surface area of the peach root system, enhance the number and growth of lateral roots, and promote the activity of SnRK1. When exogenous trehalose was applied, the growth of roots was poor. Sucrose treatment reversed the inhibitory effects of trehalose on SnRK1 enzyme activity and root growth. We also found that lateral root number of PpSnRK1a-overexpressing plants (4-1, 4-2, 4-3) increased significantly. Therefore, we believe that peach SnRK1 is involved in sucrose-mediated root growth and development. To further clarify this mechanism, we used qRT-PCR analysis to show that exogenous sucrose could promote the expression of auxin- related genes in roots, thereby leading to the accumulation of auxin in the root system. In addition, the genes related to auxin synthesis and auxin transport in the root systems of PpSnRK1a-overexpressing lines were also significantly up-regulated. Using peach PpSnRK1a as the bait, we obtained two positive clones, PpIAA12 and PpPIN-LIKES6, which play key roles in auxin signaling. The interactions between peach PpSnRK1a and PpIAA12/PpPIN-LIKES6 were verified by yeast-two-hybrid assays and bimolecular fluorescence complementation experiments, and the complexes were localized in the nucleus. After exogenous trehalose treatment, the expression of these two genes in peach root system was inhibited, while sucrose had a significant stimulatory effect and could alleviate the inhibition of these two genes by trehalose, which was consistent with the trend of sucrose's regulation of SnRK1 activity. In conclusion, peach SnRK1 can respond to sucrose and regulate root growth through auxin signal pathway. This experiment increases our understanding of the function of fruit tree SnRK1, and provides a new insight to further study sugar hormone crosstalk in the future.